Effect of hysteroscopic adhesiolysis for mild intrauterine adhesions on live birth rate following embryo transfer: a retrospective cohort study - Yu Li; Yu Dai; Mingming Deng; Hong Lv; Yanlei Dong; Lei Yan (BMC Pregnancy and Childbirth)
Abstract Background Numerous studies have demonstrated that the presence of IUAs can have detrimental effects on female reproductive function, potentially leading to infertility. Hysteroscopic adhesiolysis is widely regarded as the primary treatment for IUAs. A 2021 consensus development study on the top 10 research priorities for the future of infertility suggested that the impact on live birth rates after surgical treatment of mild IUAs is uncertain. Materials and methods The study was a retrospective cohort study that included 442 patients who were diagnosed with mild IUAs and underwent embryo transfer (fresh or frozen embryo) from January 2017 to December 2023 at a University-based reproductive medical center. Patients were divided into two groups according to whether underwent hysteroscopic adhesiolysis. The non-surgical group consisted of 204 patients, while the surgical group consisted of 238 patients. all patients underwent fresh or frozen embryo transfer. We compared the pregnancy outcomes and obstetric outcomes of the first embryo transfer after diagnosis or surgery of IUAs between the two groups. The main outcome measure is live birth rates. Between-group variances were evaluated using either the Pearson χ² test or the t-test. Multiple logistic regression analyses were applied to control for potential confounding effects. Results There were no significant differences in live birth rates of the non-surgical group and the surgical group(45.1% versus 42.0%,aOR,0.824;95%CI,0.558–1.217;P,0.330).All other pregnancy indicators showed no significant difference between the groups either. Conclusion Hysteroscopic adhesiolysis does not significantly improve the live birth rates in patients with mild IUAs. Therefore, for patients with mild IUAs, it is recommended to prioritize expectant treatment. Clinical trial number Not applicable.